Influence of beneficial bacterial inoculation on nitrogen concentration and tomato seedling growth under glasshouse conditions - Akter, Amaily; Tan, Ali Kee Zuan; Kasim, Susilawati; Mohd Amin, Adibah; Ab Aziz, Zakry Fitri; Md Rahmatullah, Noor; Rahman, Md Ekhlasur; Sadeq, Buraq Musa; Chompa, Sayma Serine (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2023)
Many types of soil bacteria through antagonistic activity, thrive in the rhizosphere of plants or surround the tissues of plants and encourage plant development and reduce the nematode population. Bacteria as such are commonly known as Plant Growth-Promoting Rhizobacteria (PGPR). The purpose of this research was to determine Bacillus spp. inoculations impact on tomato seedling development with varying rates of chemical nitrogen-fertilizer. To minimize the recommended quantity of N fertilizer for tomato seedling development, a small pot experiment with selected PGPB was undertaken with varying amount of N fertilizer. Plant growth-promoting bacteria (PGPB) labeled as UPMB10 and UPMRB9 (identified as Bacillus subtilis and Bacillus tequilensis, respectively) were utilized as microbial inoculants because they showed a significant improvement in seedling growth and N concentration in tomato plant tissues in a pot culture investigation. These microbial inoculants significantly improved the development of the plants, stem length, root length, leaves number, dry weight of shoots (stem, leaves), dry weight of roots, SPAD value, N concentration in tissues, and soil bacterial population. Bacteria-treated seedlings with 50% N fertilizer significantly increased stem length (69.07%), root length (78.51%), leaves number (68.58%), shoots (92.45%, 90.39%, stem and leaves, respectively), roots (73.33%), SPAD value (50.31%), and N concentration in plant tissues (63.79%) as compared to the uninoculated control. The findings also showed that inoculation of the Bacillus spp. tomato seedlings could save up to 50 percent of the recommended rate of chemical N fertilizer without affecting tomato seedling growth. The findings of this study suggest that the amount of nitrogen fertilizer given during tomato seedling development can be reduced by half, resulting in increased soil health and reduced environmental pollution.